Granulicatella adiacens: a rare cause of neonatal pneumonia - Ayub, Muhammad Rashid; Noor, Fatimah (Journal of Fatima Jinnah Medical University, 2019)
Granulicatella adiacens is a Gram positive, nutritionally variant streptococcus, occurring as a normal commensal in oral cavity, intestine and genitourinary tract of humans. Infections in these areas can lead to endovascular, central nervous system, oral, bone and joint and urogenital tracts infections. This case report describes a male infant found to have Granulicatella adiacens sepsis. The patient was successfully treated with combination antimicrobial therapy.